Bats of Kipot caves in Burias, Mambusao, Capiz. - Navarra, Cheryl Ferrer
A study was conducted to identify and prescribe the bat community in Kipot Caves in Burias, Mambusao, Capiz. Morphometric measurements, abundance and diversity were determined. Sampling was staggered from October to December 1998 in seven out of 24 caves in area. Sampling started shortly before dark until midnight. A 12-m long mesh net with a radius of 1.5 m was set at the entrance of the cave making sure that there was no exit for the bats other than into the net. The sampled bats were then identified and their external features measured., Of the six bat families documented in the Philippines, five were found inhabiting Kipot Cave. These are the Vespertilionidae, Rhinolophidae, Megadermatidae, Emballonuridae, and Pteropodidae. There were a total of seven genera and species recorded. Of the 190 bats collected in the caves, the most prevalent was the Vespertilionids comprising 50 (n=95) of the total bat sample while the Pteropodids as the rarest with only one sample (0.53). Generally, there was no significant difference in the length of ear, body, tail, forearm, hindfoot, and body weight of male and female bats, both among juveniles and adults. There were more adults and males. Among the bat species, Murina cyclotis was the most dominant (n=50), inhabiting six out of seven caves sampled. Phoniscus jagorii, the only fruit bat and Macroglossus minimus were the rarest species, each inhabiting only one out of seven caves, at frequency of only one each species.